Spatial Policy on Environmental Management in Gayo Lues Regency - Fadhlinsyah; Siti Hajar; Obed Bida (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Spatial planning policies must align with environmental policies to increase security and comfort, productivity, and harmony in the natural environment. This paper aims to identify and analyze the application of spatial planning policies to environmental management in Gayo Lues Regency because several community conflicts still need to carry out their business following the regulations that apply to both spatial planning and environmental policies. This study collected data through interviews with the spatial planning and environmental services and the community and business actors using a qualitative method. In addition, data collection also uses documents. The analysis technique is based on an interactive model of data collection, data reduction, presentation, and conclusion. The study results show that Gayo Lues Regency already has excellent and synergistic regulations between spatial planning and the environment. However, implementing this policy is still not optimal, so several violations by the community are found, such as disposing of waste oil indiscriminately. Some of the obstacles to implementing these policies consist of two factors. 1) External factors where some people need a high level of concern and low awareness to protect the surrounding environment. 2) From internal factors that the government itself needs to maximize in disseminating policies or is still negligent in providing educative information to the public related to protecting the environment.